STUDY ON THE PREVALENCE AND HEMATOLOGICAL ALTERATIONS IN TOXOPLASMA GONDII INFECTED CAPTIVE PHEASANT SPECIES OF BAHAWALPUR ZOO, PAKISTAN - M. H. Lashari; M. Bibi; U. Farooq; F. Afzal; A. Ali; M. Safdar 2 M. S. Akhtar; A. A. Farooq4 S. Masood5 M. Ayaz; M. I. Khan (Journal of Animal and Plant Sciences, 2020)
The purpose of this study was to identify the seroprevalence of Toxoplasma gondii (T. gondii) and hematological alterations in captive pheasant species of Bahawalpur Zoo, Bahawalpur, Pakistan. The blood samples of 100 birds belonging to three different species viz. ring-necked pheasant (Phasianus colchicus) (n=46), green pheasant (Phasianus versicolor) (n=40), and silver pheasant (Lophura nycthemera) (n=14) were analyzed through Latex Agglutination Test (LAT) and Enzyme Linked Immunosorbent Assay (ELISA). Seroprevalance through LAT in ring-necked, silver and green pheasants was 10.86%, 7.14% and 7.5%, and through ELISA was 32.60%, 22.5% and 14.28%, respectively. Adults and males had higher prevalence as compared to their counterparts, though, statistically nn-significant (P≥0.05). In all the studied species, hematological results revealed that mean values of Hb and TEC were higher (P≤0.05) in non-infected birds as compared to infected ones. This is a preliminary study of a kind and needs further research with large number of sample and population across the country.
Keywords: Toxoplasma gondii; ELISA; LAT; Seroprevalance; Oocytes; Hematology parameters